1997
DOI: 10.1136/jnnp.62.6.612
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric manifestations of neurocysticercosis: a study of 38 patients from a neurology clinic in Brazil.

Abstract: Objective-To determine the frequency and features of psychiatric morbidity in a cross section of 38 outpatients with neurocysticercosis. Methods-Diagnosis of neurocysticercosis was established by CT, MRI, and CSF analysis. Psychiatric diagnoses were made by using the present state examination and the schedule for affective disorders and schizophrenia-lifetime version; cognitive state was assessed by mini mental state examination and Strub and Black's mental status examination. Results-Signs of psychiatric dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 34 publications
3
101
1
4
Order By: Relevance
“…Our patient showed no evidence of obstructive hydrocephalus with cerebral edema as the most likely cause of her papilledema, unlike a recently reported case of neurocysticercosis in which diplopia and headache were described [11]. Small case series have suggested that mania is the most common mood disorder in neurocysticercosis; however, a larger prospective study of psychiatric disorders in 38 patients with neurocysticercosis showed that depression was most prevalent (12/23 patients with psychiatric disease, or 52%) [12].…”
Section: Discussioncontrasting
confidence: 46%
“…Our patient showed no evidence of obstructive hydrocephalus with cerebral edema as the most likely cause of her papilledema, unlike a recently reported case of neurocysticercosis in which diplopia and headache were described [11]. Small case series have suggested that mania is the most common mood disorder in neurocysticercosis; however, a larger prospective study of psychiatric disorders in 38 patients with neurocysticercosis showed that depression was most prevalent (12/23 patients with psychiatric disease, or 52%) [12].…”
Section: Discussioncontrasting
confidence: 46%
“…14 Neurocysticercosis may also be associated with inflammatory cerebral aneurysm and subarachnoid hemorrhage, 27 temporal lobe epilepsy, 31 psychiatric manifestations, 24 and stroke. Recently, a link between NCC and oncogenesis has been postulated.…”
Section: Resultsmentioning
confidence: 99%
“…A number of patients with NCC present with psychiatric and intellectual impairment symptoms [15,16].…”
Section: Clinical Featuresmentioning
confidence: 99%